PENAMBAHAN BIOCHAR BERBASIS LIMBAH PADA INCEPTISOL TERHADAP BUDIDAYA TEMBAKAU (Nicotiana tabacumL.) VARIETAS KEMLOKO DI TEMANGGUNG - Katon Sasongko Damarmoyo (Biogenesis, 2018)
ABSTRACTBiochar is a biological charcoal derived from incomplete combustion (pyrolysis) of agricultural residual materials that can increase carbon sustainably, retention of water and nutrients in soil. This research aimed to demonstrate the effect of adding biochar on inceptisol for Kemloko tobacco cultivation in Temanggung, Central Java, Indonesia. The data analysis of this research was using Factorial Random Design with two factors (treatment and dose). The results showed that the addition of biochar + compost increase productivity of 491.6 kg/ha comparing to the control with the higher tobacco quality. Chemical analysis of the respected soil showed that the biochar + compost treatment increase pH level up to 5.46 with the organic matter level and total nitrogen as well increased about 2.66% and 0.180% respectively.Keywords:  biochar, tobacco of kemloko variety, temanggung, soil chemical